How to Purchase a Woman? Status of Christian Batak Women in Marriage Tradition - Manurung, Nurseli Debora (Jurnal Perempuan, 2015)
This paper shows encounter of two traditions in marriages (Christianity-based and Batak Tradition-based), both are marginalizing women status. Church tradition and Toba Batak tradition are both patriacharl. They have different background contexts, but both subordinate women. The texts which is often used in liturgical marriage tradition describe women as those being led by men, thus led by God. In Toba Batak traditional marriages, a term called sinamot means as paying marriages. Many people say that sinamot is tuhor ni boru, literally means “woman-buying money.” Based on the roles of women and based on human rights of women, women are not dituhor, are not bought.